Daily rhythms of glucose, insulin, and nonesterified fatty acid responses to an intravenous glucose tolerance test in dairy cows - Anay D. Ravelo; Cesar Matamoros; Kevin J. Harvatine; Isaac J. Salfer (Journal of Dairy Science)
ABSTRACT: In nonruminant species, glucose tolerance and insulin sensitivity are known to be regulated by circadian rhythms, which are repeating ∼24-h cycles that govern many aspects of behavior, physiology, and metabolism. However, it is unknown if these rhythms exist in dairy cows. Our objective was to determine the fit of a daily rhythm of glucose, insulin, and nonesterified fatty acid (NEFA) clearance rates independent of daily patterns of nutrient intake. To accomplish our objective, 12 multiparous lactating Holstein cows were enrolled in a within-subject design conducted over 2 experimental periods (n = 6/period). Within each period, cows were subjected to intravenous glucose tolerance tests (IVGTT) at 4 timepoints, representing different times of the day (0300, 0900, 1500, and 2100 h). The 0900 and 2100 h IVGTT were performed 36 h apart, followed by a 7-d washout, and then the 1500 and 0300 h IVGTT were performed 36 h apart. Cows were fed 12 times/d at 2-h intervals beginning 24 h before the first IVGTT in each set until the second IVGTT in each set to stabilize feed intake across the day, with 1 time/d feeding occurring during the washout period. For each IVGTT, 250 g of glucose was infused as a 50% (wt/vol) d-glucose solution via a jugular catheter and blood was collected at −15, −5, immediately before, 0, 5, 10, 15, 20, 30, 45, 60, 90, and 120 min relative to infusion. A linear mixed model with the fixed effects of cosine and sine and random effect of cow within period was used for the outcomes of clearance rate, half-life, baseline concentration, time to baseline concentration, and area under the curve (AUC) for glucose, insulin, and NEFA. A zero-amplitude test was used to determine the fit of a 24-h cosine function and cosinor rhythmometry was used to determine the amplitude and acrophase of the 24-h rhythm. Insulin concentrations at baseline followed a diurnal rhythm. Glucose and insulin clearance rate, half-life, and AUC also followed a diurnal rhythm. Glucose and insulin clearance rates peaked at 1247 h and 0944 h, respectively. No circadian rhythm was detected for plasma NEFA concentrations. Results suggest that insulin-stimulated glucose uptake is controlled differently throughout the day by circadian rhythms.